Analisis Budaya Pekandangan : Sistem Beternak Kerbau Berkelanjutan di Kecamatan Cerenti dan Singingi Kabupaten Kuantan Singingi - Afrawati, Aida; Saam, Zulfan; Tarumun, Suardi (Dinamika Lingkungan Indonesia, 2014)
Buffalo breeding system in pekandangan culture in Kuantan Singingi Regencycontains diversity patterns of adaptation to the environment and the values of local wisdomwhich is a form of knowledge that is combined with traditional norms, cultural values andenvironmental management activities that guide the community in meeting the needs of liveand interact with their environment is still very relevant to the current conditions, and shouldbe preserved, adapted or even developed further in accordance with the concept ofsustainability. This study aims to analyze the forms of local wisdom in pekandangan culturein accordance with the concept of sustainable buffalo breeding systems, analyze activity andcultural barriers in pekandangan culture, and analyze public perceptions of the pekandanganculture. The method used in this study is a qualitative research method approach. Datacollection using observation, interview and documentation. In-depth interviews conductedwith key informants: breeders, chairman of the group of pekandangan, traditional leaders,community leaders, village chiefs and Dinas Peternakan of Kuantan Singingi Regencyofficials. Structured interview was conducted to determine the public perception of therespondents were community residing 0.5-3 km of pekandangan area.The results of the studyas follows: (1) The forms of local wisdom in accordance with the concept of sustainablebuffalo breeding systems in the pekandangan culture is cage architecture uses the directsunlight, the cage material is made of organic or renewable materials, utilizing buffalo dunginto manure, bonfire material from organic ingredients, free fodder pesticides, buffalograzing by means of foot, and the existence of regular meeting of pekandangan groups /societies and mutual help activities. (2) Public perception of pekandangan culture is goodbecause it provides benefits and economic advantages, can improve people's lives and have asocial system.